2010
DOI: 10.29333/ejgm/82877
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Abscess of the Chest Wall

Abstract: Chest wall is a rare involvement localization of tuberculosis, though uncommon are frequently seen in countries endemic to the disease. In this report, a tuberculosis case with chest wall involvement is presented. Key words: Tuberculosis, cold abscess, chest wall Göğüs Duvarının Tüberküloz AbsesiHastalığın endemic olarak görüldüğü yerlerde bile göğüs duvarı tutulumu sık değildir, nadir tüberkuloz tutulum lokalizasyonudur. Bu bildiride, göğüs duvarı tutulumu olan bir vaka sunulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Il s'agit très souvent d'une localisation survenant au cours d'une tuberculose grave et disséminée [ 1 ]. La dissémination hématogène, lymphatique ou par contiguïté est évoquée [ 1 , 2 , 4 , 16 21 ]. En milieu agricole, l´éventualité d´une inoculation directe transcutanée au niveau de la paroi thoracique est envisagée.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Il s'agit très souvent d'une localisation survenant au cours d'une tuberculose grave et disséminée [ 1 ]. La dissémination hématogène, lymphatique ou par contiguïté est évoquée [ 1 , 2 , 4 , 16 21 ]. En milieu agricole, l´éventualité d´une inoculation directe transcutanée au niveau de la paroi thoracique est envisagée.…”
Section: Discussionunclassified
“…La prévalence est plus élevée chez l´adulte jeune, entre 15 et 35 ans, et exceptionnelle chez l´enfant, même en zone de forte endémie tuberculeuse[ 7 , 16 , 23 ]. Elle peut survenir aussi chez le sujet âgé de plus de 50 ans souvent porteur de multiples comorbidités, terrain propice pour le développement de cette affection [ 9 , 16 ]. Dans notre série, la moyenne d’âge de nos patients était de 34 ans, ce qui rejoignait celle de la grande série de Paik et al [ 18 ] et qui était de 33,3 ans.…”
Section: Discussionunclassified
“…In a study, only 4 of 18 patients with tuberculous abscess of the chest wall could be diagnosed with FNAB, and another study reported the rate of diagnosis with FNAB as 36% [3]. In a serial study on FNAB samples; diagnosis was made by AFB smear in 35% and by culture positivity in 60% of the cases [7]. In our patient, diagnosis was made by histopathological and microbiological examination of the FNAB samples, and also during surgery performed for removing the affected tissues, samples were sent to frozen section examination.…”
Section: Discussionmentioning
confidence: 99%